The power of C++ - Ehman, Ashley (The power of coding, 2018)
This book introduces readers to important concepts like object-oriented programming while elaborating on the history of the C++ computer programming language, provides examples of code, and explores the relationship between C++, C, and C#. Full-color photographs, a glossary, an index, and sidebars are also included.--Provided by publisher.